2016
DOI: 10.1002/anie.201603676
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Hydrogen Bond Dynamics of Bulk‐like and Bound Water at Positively and Negatively Charged Lipid Interfaces Revealed by 2D HD‐VSFG Spectroscopy

Abstract: Interfacial water in the vicinity of lipids plays an important role in many biological processes, such as drug delivery, ion transportation, and lipid fusion. Hence, molecular‐level elucidation of the properties of water at lipid interfaces is of the utmost importance. We report the two‐dimensional heterodyne‐detected vibrational sum frequency generation (2D HD‐VSFG) study of the OH stretch of HOD at charged lipid interfaces, which shows that the hydrogen bond dynamics of interfacial water differ drastically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 50 publications
7
86
1
Order By: Relevance
“…These fast and slow components are assigned to hydrogen‐bond fluctuations and hydrogen‐bond rearrangements, respectively . Because the ultrafast hydrogen‐bond fluctuations (≈60 fs) cannot be directly detected with the time resolution (≈200 fs) of the present 2D HD‐VSFG experiments, this fast fluctuation is expected to result in only a small initial CLS value . Therefore, the small initial CLS value indicates a large contribution from the fast hydrogen‐bond fluctuations whereas a large initial CLS value implies its suppression.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…These fast and slow components are assigned to hydrogen‐bond fluctuations and hydrogen‐bond rearrangements, respectively . Because the ultrafast hydrogen‐bond fluctuations (≈60 fs) cannot be directly detected with the time resolution (≈200 fs) of the present 2D HD‐VSFG experiments, this fast fluctuation is expected to result in only a small initial CLS value . Therefore, the small initial CLS value indicates a large contribution from the fast hydrogen‐bond fluctuations whereas a large initial CLS value implies its suppression.…”
Section: Resultssupporting
confidence: 79%
“…In our previous 2D HD‐VSFG study on the cationic DPTAP (1,2‐dipalmitoyl‐3‐trimethyl ammonium propane) and anionic DPPG (1,2‐dipalmitoyl‐ sn ‐glycero‐3‐phosphorylglycerol) lipid/HOD–D 2 O interfaces, we reported that the initial CLS of the DPTAP (0.29±0.04) and DPPG (0.80±0.03) interfaces are significantly different from each other. This difference was attributed to the difference in the hydrogen bonds between the lipid head groups and interfacial water, because the choline moiety of the DPTAP cannot form any hydrogen bonds whereas the phosphoglycerol moiety of DPPG forms strong hydrogen bonds with interfacial water.…”
Section: Resultssupporting
confidence: 79%
“…The water at the negatively charged biomolecule surface is oriented with the hydrogens of the O–H modes pointing on average toward the air (up). 86 …”
Section: Discussionmentioning
confidence: 99%
“…Work on DPTAP showed only a single broad peak when studied with D 2 O and HOD. 6,8 Overall, the discussion of the origin of the cross-peak is out of the scope of this paper. Instead, the goal of this work is to investigate and highlight the possible effects of interfacial water orientation on interfacial vibrational water dynamics.…”
Section: D-sfg Spectramentioning
confidence: 99%
“…For negative (positive) lipids, the water dipole points towards (away from) the lipid layer, exhibiting an ultrafast relaxation path available only for the positively charged lipid. [6][7][8] In the case of the negatively charged surfactant sodium dodecyl sulfate (SDS) water interface two types of water were reported. 9 Given the ubiquitous presence of the lipid/water interface, these kinds of differences in vibrational dynamics -that reflect differences in structure 10 -could be important for the functionality of lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%